Fostering innovative workforce behavior through transformation leadership: a case study among enterprise 50 award companies - Noor, Haris Md; Adi, Mohd Nazir Mohd; Kamaruddin, Nor Kamariah (American Scientific Publishers, 2018)
Innovative and creative capacities are essential determinants of economic prosperity in globalized knowledgebased economy. This helps to transform the SMEs and country economy, in stimulating stabilize, growth and competition among SMEs. The question is how these SMEs E50s survive and sustain their existence in market through leadership and encouraging innovative workforce. The objectives of the study is to determine the relationship between transformational leadership practices in encouraging innovative workforce behaviours among the E50s. The research involved Top Ten E50s award winners from the year 2011–2013, in the position of middle management level at the operation site. A quantitative was later employed to analyse the data which comprises of the four dimension of transformational leadership towards encouraging innovative workforce behaviours. The results showed that the four dimension of transformational leadership practices has a strong relationship with innovative workforce bahaviours with overall r > 0.631. It is proof that transformational leadership practices will be a good guideline for other SMEs to adapt this dimension of leadership practices in encouraging innovative workforce behavior among their workers as to be competitive and listed among the E50s Award winning SMEs.